Marker based standardization of polyherbal formulation (SJT-DI-02) by high performance thin layer chromatography method - Ladva, Bhakti J. (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Preparation of highly standardized herbal products with respect to chemical composition and biological activity is considered to be a valuable approach in this field. SJT-DI-02 polyherbal formulation was successfully developed at our institute and filed for patent at Mumbai patent office. OBJECTIVE: The present work was marker based standardization of patented, novel and efficacious polyherbal formulation namely SJT-DI-02 for the treatment of diabetes. The SJT-DI-02 was comprised of dried extracts of rhizomes of Acorus calamus, leaves of Aegle marmelose, fruits of Benincasa hispida, roots of Chlorophytum arendinaceum, seeds of Eugenia jambolana, leaves of Ocimum sanctum, pericarp of Punica granatum, seeds of Tamarindus indica. Selected plants were collected, dried and extracted with suitable solvents. The formulation was prepared by mixing different fractions of extracts. MATERIALS AND METHODS: For successful and best standardization, first of all selection and procurement was carried out. Selection is done on the basis of therapeutic efficacy and amount of the marker present in the particular plant part. At the time of procurement side by side phytochemical screening and estimation of phytoconstituents was carried out. After completion of preliminary screening using characterized markers, we tried to develop best TLC systems using selected solvent composition. Finally well-developed TLC systems were applied in HPTLC. In the present study polyherbal formulation was standardized by using different four markers. TLC Densitometric methods were developed using HPTLC for the quantification of these marker compounds. Solvent systems were optimized to achieve best resolution of the marker compounds from other components of the sample extract. The identity of the bands in the sample extracts were confirmed by comparing the R(f) and the absorption spectra by overlaying their UV absorption spectra with those of their respective standards. The purity of the bands due to marker compounds in the sample extracts were confirmed by overlaying the absorption spectra recorded at start, middle and end position of the band in the sample tracks. After conforming all these things fingerprints were developed for all three formulations which will be act as authentification and quality control tool. RESULTS: % w/w of asarones is 3.61, % w/w of marmelosin is 4.60, % w/w of gallic acid is 10.80 and % w/w of lupeol is 4.13. The method was validated in terms of linearity, precision, repeatability, limit of detection, limit of quantification and accuracy. In well-developed mobile phase system linearity was found to be in the range of 0.983-0.995, % recovery was found to be in the range of 97.48-99.63, % RSD for intraday and interday was found to be 0.13- 0.70 and 0.32 -1.41 and LOD and LOQ was found to be in the range of 0.15- 0.61 and 0.45 -1.83 microgram per ml. CONCLUSION: Thus High performance thin layer chromatography (HPTLC) methods were developed and validated in terms of linearity, precision, repeatability, limit of detection, limit of quantification and accuracy. The methods were rapid, sensitive, reproducible and economical. It does not suffer any positive or negative interference due to common other component present in the formulation and would also serve as a tool for authentication of herbal products containing marmelosin, gallic acid, lupeol and asarones. Thus this work provides standardized and therapeutically active polyherbal formulations for the different ailments.